Predominant and novel de novo variants in 29 individuals with ALG13 deficiency: Clinical description, biomarker status, biochemical analysis, and treatment suggestions. Issue 6 (5th August 2020) - Ng, Bobby G.; Eklund, Erik A.; Shiryaev, Sergey A.; Dong, Yin Y.; Abbott, Mary‐Alice; Asteggiano, Carla; Bamshad, Michael J.; Barr, Eileen; Bernstein, Jonathan A.; Chelakkadan, Shabeed; Christodoulou, John; Chung, Wendy K.; et al.
Abstract: Asparagine‐linked glycosylation 13 homolog ( ALG13 ) encodes a nonredundant, highly conserved, X‐linked uridine diphosphate (UDP)‐ N ‐acetylglucosaminyltransferase required for the synthesis of lipid linked oligosaccharide precursor and proper N‐linked glycosylation. De novo variants in ALG13 underlie a form of early infantile epileptic encephalopathy known as EIEE36, but given its essential role in glycosylation, it is also considered a congenital disorder of glycosylation (CDG), ALG13‐CDG. Twenty‐four previously reported ALG13‐CDG cases had de novo variants, but surprisingly, unlike most forms of CDG, ALG13‐CDG did not show the anticipated glycosylation defects, typically detected by altered transferrin glycosylation. Structural homology modeling of two recurrent de novo variants, p.A81T and p.N107S, suggests both are likely to impact the function of ALG13. Using a corresponding ALG13‐deficient yeast strain, we show that expressing yeast ALG13 with either of the highly conserved hotspot variants rescues the observed growth defect, but not its glycosylation abnormality. We present molecular and clinical data on 29 previously unreported individuals with de novo variants in ALG13 . This more than doubles the number of known cases. A key finding is that a vast majority of the individuals presents with West syndrome, a feature shared with other CDG types. Among these, the initial epileptic spasms best responded to adrenocorticotropic hormone or prednisolone, while clobazam and felbamate showed promise for continued epilepsy treatment. A ketogenic diet seems to play an important role in the treatment of these individuals.